Bersinar Ditengah Kegelapan: Analisis Nilai-Nilai Kepemimpinan Rengoku Kyojuro Dalam Anime Kimetsu No Yaiba “Arc Mugen Train” - Ariefin, Moch. Irsyad; Erniati, Erniati; Amin, Sagir Muhammad; Anirah, Andi (Vocational College of Diponegoro University, 2026)
This research is motivated by fictional characters in the anime Kimetsu no Yaiba arc Mugen Train, apart from being an entertainment medium can also be used as a means of character formation for students, especially in terms of leadership. This study aims to analyze the leadership values that have been displayed by the main character, namely Rengoku Kyojuro in the Kimetsu no Yaiba arc Mugen Train. This research uses a descriptive qualitative method with narrative analysis, through scenes, dialogues, and studies on leadership theory. The results of this study show that Rengoku Kyojuro has five main dimensions of leadership, including courage, sacrifice, exemplary, empathy, and commitment to the principles of life. The findings of this study also indicate that the figure of Rengoku Kyojuro is a leader whose speech and actions are in line with modern leadership theories, including transformational leadership, servant leadership, principle centered leadership, emotional intelligence leadership, and steward leadership. The anime Kimetsu no Yaiba arc Mugen Train really presents a story, where the main character has concrete leadership values so that it can be used as an example for students in character formation.